PERAN NEGARA DALAM HISBAH - Mujahidin, Akhmad (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
This article is a review of the theoretical hisbah authority and how the State has a role in it. The most important role of the state in the implementation of technically hisbah that muhtasib task is holding the governor of executive power, legal power of the district court, as well as regional police powers. Muhtasib have a responsibility for the welfare of Islamic society. Islam concerns in world and hereafter to build human welfare. Therefore, muhtasib jurisdiction is not limited. Muhtasib attention is on what is specified by Allah and all that is legally recognized as a man desires.DOI: 10.15408/aiq.v4i1.2544